Evaluasi Kinerja Aparatur Berbasis Teknologi Digital untuk Meningkatkan Efektivitas Layanan Administrasi Publik Modern - Asriyani; Zakky Zamrudi; Syahrial Shaddiq (Indonesia Economic Journal, 2025)
This study aims to analyze the application of digital technology in the performance evaluation process of civil servants and its impact on the effectiveness of modern public administration services. The urgency of this study is based on the demands of bureaucratic transformation in the digital era, which requires government officials to be able to work faster, more accurately, and more accountably. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation studies of the performance evaluation process that takes place in the sub-district bureaucracy. The results of the study show that the use of digital technology, such as online attendance applications, personnel information systems, and internet-based communication media, can improve the accuracy of performance assessments, speed up reporting, and strengthen coordination between officials. The findings also reveal that the use of digital technology contributes to increased transparency, work efficiency, and the quality of public administration services, even though a number of obstacles are still encountered, such as limited digital literacy and internet infrastructure. Overall, this study concludes that the digitization of civil servant performance evaluations is an effective strategy in promoting the modernization of public services and strengthening bureaucratic accountability, and therefore needs to be optimized through capacity building among civil servants and the development of more adequate technological facilities.